Survival in a collapsing economy: a case study of informal trading at a Zimbabwean flea market - Tamukamoyo, Hamadziripi (My University, 2010)
Abstract The central concern of this study is the nature of informal economic activities among urban traders in Harare, Zimbabwe. The study focuses on a particular flea market and describes the precarious lives of a sample of informal traders. It is shown that, as through much of Africa, the market is a social as well as an economic nexus. It is not only the site of economic production and exchange constituting the survivalist activities that are increasingly important in the collapsing Zimbabwe economy, but also the site of diverse social relations. The thesis also shows that the formal and informal are part of the same deeply segmented economy and not two distinct, separate economies. The extended case study method is used to describe and analyse the nature of informal trading activities among traders dealing in four types of goods commonly found at the flea market: clothes and shoes, DVDs and video games, arts and crafts, and second-hand books. Primary and secondary sources, interviews with policy experts, researchers and activists, a total of 70 semi-structured interviews with traders and participant observation, over a period of one and a half years were used to obtain data on the nature of the informal economy in the current Zimbabwe crisis, and to profile these traders. The thesis describes the daily lives of the traders, their social characteristics and work histories, and the social relations of trust and reciprocity which enable them to source their goods. It is shown that the majority of the traders live an extremely precarious existence marked by low, unstable incomes. However, they should not be viewed as passive victims of the economic crisis, as they demonstrate qualities of resourcefulness and innovation. Nor are they totally excluded from global circuits of production and exchange. Global connections are identified and shown to be relevant to the sourcing and sale of goods. These connections suggest an alternative way of conceptualising globalisation.
Keywords: informal economic activities; informal traders; Harare, Zimbabwe; globalisation; extended case method; localisation of the global; globalisation of the local; social networks